Men writing eating disorders : autobiographical writing and illness experience in English and German narratives - Bartel, Heike (Emerald points., 2020)
Eating disorders do not only affect women and girls; men and boys get them too but remain mostly invisible. This book gives insight into this neglected problem through a comparative and transnational analysis of autobiographical accounts written by men with experience of living with eating disorders.